Analisis Teknik Dasar Pemain Futsal Tim Prasetya United Lubuklinggau - Ronny Martin; Yohana Satinem; Azizil Fikri (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
This study aims to determine the results of research that has been carried out by researchers with reference techniques of observation, interviews, and documentation with the coach and the Prasetya United team, totaling 24 people on the Futsal Field consisting of the coach, assistant coach, and the Prasetya United team. In the first data analysis, the researcher conducted interviews with the trainers by recording. Then the second stage of data reduction, the researcher made a transcript of the interview and then changed the data into written form. The third stage presents the data. The data is submitted by clarifying and identifying the data in the form of interview transcripts and a brief description. Then the fourth stage is drawing conclusions and verification. The results of this research are that some of the players who are members of the Pratsetya United team have mostly mastered futsal game techniques such as passing, control, chipping, dribbling, shooting techniques, and heading the ball. In conclusion, most of the players on the Prasetya United futsal team have mastered the techniques of futsal Keywords: Futsal Basic Techniques